Marketing entry strategy for Agropromkomplektatsiya in Vietnam - Babicheva, Anna (2022)
The main objective of the thesis is to analyze the Vietnamese market in regards to a market entry of the Russian company “APK”. The company is forced to expand according to the fact that Russian pork market is already saturated. Vietnam is one of the first countries which APK has chosen for expansion. The thesis contains of two parts, which are theoretical and practical. The theoretical part contains information about the agricultural industry, its specifics, expansion and export policy. In the practical part, using secondary data and research of different consulting companies, the author examines the Vietnamese market of meat. According to the market research, the author created a marketing entry strategy for APK company. The strategy includes the mode of entry, marketing goals, SWOT, STP model, branding and marketing mix 4Ps.